Analisis kemampuan operasional guru dalam literasi digital pada implementasi kurikulum merdeka di Sekolah Dasar - Mubarok, Nanda Dhiemas Dwi; Marmoah, Sri; Supianto, Supianto (Didaktika Dwija Indria, 2024)
This research is entitled Analysis of Teacher Capabilities in Digital Literacy in the Implementation of the Merdeka Curriculum at Leran Wetan I Palang Tuban Elementary School. The aim of this research is to describe teachers' abilities in digital literacy in the implementation of the Independent Curriculum at Leran Wetan I Palang Tuban Elementary School. This research uses a qualitative approach with descriptive methods. Data collection techniques use observation, interviews and questionnaires. The research results show that teachers have operational abilities in digital literacy. The conclusion of this research is that teachers master operational skills in digital literacy.